Polycentrism in the Spanish metropolitan system: an analysis for 7 metro areas - Carlos Marmolejo Duarte; Carlos Aguirre Nu\~nez; Eduardo Chica Mejia; Claudia Perez Prieto; Jaume Masip Tresserra (European Regional Science Association (ERSA), 2011)
Polycentrism is becoming one of the dominant structures in contemporary metropolises. Concentrated decentralization and the integration of formerly independent cities by the reduction of travel time are behind of such a process. In this paper, the spatial structure of the seven biggest metro areas in Spain is depicted. By analyzing employment density and travel-to-work data the polycentric structure of them is detected at the time that the functional borders are delimited. Results suggest a very heterogeneous image where Barcelona and Bilbao emerge as the most polycentric areas at the time that Madrid, Seville and Zaragoza have a structure more orientated towards monocentrism. Clearly polycentric structure seems to be influenced by the orographic nature in which each metropolitan area lays in.
Keywords: 330